2014
DOI: 10.1128/jvi.01145-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypervariable Region 1 for the Interplay of Hepatitis C Virus with Entry Factors and Lipoproteins

Abstract: Hepatitis C virus (HCV) particles associate with lipoproteins and infect cells by using at least four cell entry factors. These factors include scavenger receptor class B type I (SR-BI), CD81, claudin 1 (CLDN1), and occludin (OCLN). Little is known about specific functions of individual host factors during HCV cell entry and viral domains that mediate interactions with these factors. Hypervariable region 1 (HVR1) within viral envelope protein 2 (E2) is involved in the usage of SR-BI and conceals the viral CD81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 55 publications
6
61
2
Order By: Relevance
“…These results are in line with those recently reported by Bankwitz et al (48). In addition, these authors also showed that HVR1 deletion does not affect the content of apoE associated with the virion (48). Furthermore, in line with the results of Jiang et al (29), the findings of our kinetic analysis of HCV entry in the presence of anti-apoE antibody and the capacity of the anti-apoE antibody to inhibit virion binding to cells are other arguments supporting the role of apoE in binding to HS.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…These results are in line with those recently reported by Bankwitz et al (48). In addition, these authors also showed that HVR1 deletion does not affect the content of apoE associated with the virion (48). Furthermore, in line with the results of Jiang et al (29), the findings of our kinetic analysis of HCV entry in the presence of anti-apoE antibody and the capacity of the anti-apoE antibody to inhibit virion binding to cells are other arguments supporting the role of apoE in binding to HS.…”
Section: Discussionsupporting
confidence: 83%
“…Although JFH1-⌬HVR1 was more sensitive to neutralization by the anti-apoE polyclonal antibody, no difference was observed with two different MAbs. These results are in line with those recently reported by Bankwitz et al (48). In addition, these authors also showed that HVR1 deletion does not affect the content of apoE associated with the virion (48).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations